2009
DOI: 10.1007/s10557-009-6198-z
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Supplementation Gender Independently Improves Endothelial Reactivity and Suppresses Superoxide Production in Healthy Rats

Abstract: Our results suggest that resveratrol supplementation gender independently could improve the capacity of endothelial function and suppression of oxidative stress under physiological conditions. Resveratrol ingestion indicates a potential for cardiovascular health promotion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…It is postulated that Res probably reduces the deleterious effect of oxidative stress in living cells due to its ability to 1) compete with co-enzyme Q and decrease mitochondrial ROS production, 2) scavenge superoxide radicals, 3) inhibit lipid peroxidation induced by Fenton reactions, and 4) regulate the expression of antioxidant co-factors and enzymes (Pervaiz & Holme 2009). In addition, some studies demonstrated that Res inhibits NADPH oxidase activity and expression, which is a major contributor to superoxide radical production causing local oxidative stress (Soylemez et al 2009, Spanier et al 2009). Along with a decrease in lipid peroxidation, resveratrol also induced a small but significant increase in protein and a higher increment (3 .…”
Section: Discussionmentioning
confidence: 99%
“…It is postulated that Res probably reduces the deleterious effect of oxidative stress in living cells due to its ability to 1) compete with co-enzyme Q and decrease mitochondrial ROS production, 2) scavenge superoxide radicals, 3) inhibit lipid peroxidation induced by Fenton reactions, and 4) regulate the expression of antioxidant co-factors and enzymes (Pervaiz & Holme 2009). In addition, some studies demonstrated that Res inhibits NADPH oxidase activity and expression, which is a major contributor to superoxide radical production causing local oxidative stress (Soylemez et al 2009, Spanier et al 2009). Along with a decrease in lipid peroxidation, resveratrol also induced a small but significant increase in protein and a higher increment (3 .…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol has vasoprotective effects in several experimental models due to suppression of NADPH oxidase and activation of SIRT1-dependent mechanisms [7,9,10]. In healthy rats, resveratrol was found to increase endothelial function by suppressing NAD(P)H-dependent superoxide production [8,11]. Moreover, resveratrol improves endothelial relaxation to acetylcholine by increasing levels of eNOS mRNA and eNOS phosphorylation in obese and type 2 diabetic mice [9,12].…”
Section: Introductionmentioning
confidence: 99%
“…However, relaxations of vessels isolated from normotensive animals were augmented by resveratrol. A similar effect of resveratrol on vessels isolated from normotensive animals had been examined in Wistar rats [16] but not in Sprague-Dawley rats [5]. Thus, these results represented that the effect of resveratrol on the endotheliumdependent relaxation was related to animal species and hypertension models.…”
Section: Discussionmentioning
confidence: 66%
“…ADMA is an endogenous competitive inhibitor of NO synthase and increased level of ADMA causes NO reduction in different types of hypertension [16,19,22]. However, the blood ADMA level was not determined in DOCA salt-induced hypertension of rats.…”
Section: Discussionmentioning
confidence: 99%